Characteristic microglial features in patients with hereditary diffuse leukoencephalopathy with spheroids. Issue 4 (4th September 2016) - Tada, Mari; Konno, Takuya; Tada, Masayoshi; Tezuka, Toshiyuki; Miura, Takeshi; Mezaki, Naomi; Okazaki, Ken‐ichi; Arakawa, Musashi; Itoh, Kyoko; Yamamoto, Toru; Yokoo, Hideaki; Yoshikura, Nobuaki; et al.
Abstract : Objective: To clarify the histopathological alterations of microglia in the brains of patients with hereditary diffuse leukoencephalopathy with spheroids (HDLS) caused by mutations of the gene encoding the colony stimulating factor‐1 receptor ( CSF‐1R ). Methods: We examined 5 autopsied brains and 1 biopsy specimen from a total of 6 patients with CSF‐1R mutations. Detailed immunohistochemical, biochemical, and ultrastructural features of microglia were examined, and quantitative analyses were performed. Results: In layers 3 to 4 of the frontal cortex in HDLS brains, microglia showed relatively uniform and delicate morphology, with thin and winding processes accompanying knotlike structures, and significantly smaller areas of Iba1 immunoreactivity and lower numbers of Iba1‐positive cells were evident in comparison with control brains. On the other hand, in layers 5 to 6 and the underlying white matter, microglia were distributed unevenly; that is, in some areas they had accumulated densely, whereas in others they were scattered. Immunoblot analyses of microglia‐associated proteins, including CD11b and DAP12, revealed that HDLS brains had significantly lower amounts of these proteins than diseased controls, although Ki‐67–positive proliferative microglia were not reduced. Ultrastructurally, the microglial cytoplasm and processes in HDLS showed vesiculation of the rough endoplasmic reticulum and disaggregated polyribosomes, indicating depression of protein synthesis. On the other hand, macrophages were immunonegative for GLUT‐5 or P2ry12, indicating that they were derived from bone marrow. Interpretation: The pathogenesis of HDLS seems to be associated with microglial vulnerability and morphological alterations. Ann Neurol 2016;80:554–565